Is Gender Selection Compatible with Islamic Ethics? (International Journal of Psychosocial Rehabilitation, 2020)
Gender or sex selection is performed for medical and social reasons. The issue of gender selection has created controversy when it comes to ethical aspects and Islamic legal perspectives. This happens when it involves the moral value of the unwanted fetus and the concept of ridha (contentment) with Allah’s decree. However, there are medical justifications that require this procedure to be performed. Accordingly, the article aims to analyze the gender selection procedure performed through the pre-implantation genetic diagnosis (PGD) procedure based on the code of medical ethics. It also addresses this issue from the perspective of maqasid al-shariah (objectives of Islamic law). This qualitative study reviewed medical documents related to gender selection procedures, namely general guidelines, manuals, and codes of medical ethics. The data collected were analyzed according to the themes consistent with the objectives of the study. This study found that the ethical issues and preservation of life are more dominant compared to the need for selecting fetal gender. The protection of the soul is daruriyyat (essential), while choosing the desired fetal gender is tahsiniyyat (desirable or embellishment). However, gender selection as a measure to hifz al-nafs (preservation of soul) is permitted within the limited scope. The harmony between medical needs and the evaluation of al-shariah aspects is the first measure that needs to be analyzed before the fetal gender selection procedure is performed.